Neuromuscular electrical stimulation effect on mRNA expression of skeletal muscle in elderly: NMES on mRNA expression of skeletal muscle in elderly - Jiang, Qingchun; Wei, Ruixue; Gong, Leilei; Zhao, Ruiying (Cellular and Molecular Biology, 2022)
Considering the increasing number of elderly in the world, this research aimed to investigate the effect of neuromuscular electrical stimulation (NMES) on changes in muscle mRNA abundance of a number of gene targets for improving the balance of the elderly. Twenty-six elderly undertook 30 minutes of quadriceps NMES (50 Hz, current at the limit of tolerance). Vastus lateralis muscle biopsies were obtained at rest immediately before and 24 hours after the intervention. The expression of 384 targeted mRNA transcripts was assessed by Real-time TaqMan PCR. A significant change in expression from baseline was determined using the ΔΔCT method with a false discovery rate (FDR) of <5%. The results showed that the biological functions of upregulated genes included muscle protein turnover, hypertrophy, inflammation, and muscle growth, while downregulated genes included mitochondrial and cell signaling functions. In general conclusion, it can be said that NMES can improve balance in the elderly. Therefore, considering the importance of balance in old people, it is suggested to use this method to improve the balance of the elderly.